2021
DOI: 10.1111/jocs.15758
|View full text |Cite
|
Sign up to set email alerts
|

Robotic mitral valve operations can be safely performed in obese patients

Abstract: Introduction Robotic cardiac surgery offers mitigated risks for obese patients requiring mitral valve surgery. We aimed to study the safety of robotic mitral surgery in the obese patient population by analyzing the outcomes of mitral surgery patients in our center for robotic cardiac surgery. Method This study retrospectively included 123 consecutive patients who underwent robotic mitral valve operations in a single center for robotic cardiac surgery. Patients with body mass index (BMI) ≥ 30 were compared agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Although it is well known that patients with obesity are at increased risk for postoperative complications, 6 there is recent evidence to suggest that patients with a high body mass index have similar outcomes when undergoing robotic cardiac surgery. 7 The clinical preoperative variables did not differ significantly between the cohorts over time, and although the complexity of techniques increased, there was no impact on morbidity or mortality ( Table 1 ). Complex subvalvular procedures included papillary muscle trunk repositioning (5.1%; 51/1024), division of secondary anterior chordae (56.7%; 581/1024), septal myomectomy (5.4%; 55/1024), and resection of abnormal LV muscle bands (8.3%; 83/1024).…”
Section: Resultsmentioning
confidence: 96%
“…Although it is well known that patients with obesity are at increased risk for postoperative complications, 6 there is recent evidence to suggest that patients with a high body mass index have similar outcomes when undergoing robotic cardiac surgery. 7 The clinical preoperative variables did not differ significantly between the cohorts over time, and although the complexity of techniques increased, there was no impact on morbidity or mortality ( Table 1 ). Complex subvalvular procedures included papillary muscle trunk repositioning (5.1%; 51/1024), division of secondary anterior chordae (56.7%; 581/1024), septal myomectomy (5.4%; 55/1024), and resection of abnormal LV muscle bands (8.3%; 83/1024).…”
Section: Resultsmentioning
confidence: 96%
“…Keeping in mind that the risk profile of our patients has dramatically increased in the last decade, the efforts for preventing any kind of operative complication should be accepted as a must. This percutaneous approach is especially beneficial in obese patients and enables a safe peripheral cannulation ( 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies support the safety of this innovative approach. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] In addition to confirming the safety of robot-assisted MV surgery, some of these studies have demonstrated that ROB can be used in patients with previous sternotomies, 25 those with a high body mass index, 27 the elderly, 28 those with complex valvular pathologies, 29 and in concomitant procedures. 30,34 Indeed, there is also evidence that ROB can be undertaken in lower volume 24 and nonacademic centers without compromising outcomes.…”
Section: Discussionmentioning
confidence: 99%